Actualization the Role of Women in Implementing the Green Economy to Improve Community Welfare - Suprianik Suprianik (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This research aims to analyze the actualization of women's roles in implementing the green economy concept through waste management to improve community welfare. To answer this objective, a qualitative research design was used with data collection methods using interviews and documentation. The research results show that the green economy concept can have a positive impact on community welfare. By implementing a sustainable approach that emphasizes reduction, recycling and efficient use of resources, we can create new jobs and reduce negative impacts on the environment and improve the quality of life of society as a whole. Apart from that, waste management that prioritizes green aspects can also generate additional sources of income for women through the sale of recycled materials. Thus, actualizing the role of women in implementing the green economy concept not only prioritizes environmental sustainability, but also provides benefits for family welfare and community life.